1988
DOI: 10.1093/jac/22.supplement_c.65
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of ofloxacin, desmethyl ofloxacin and ofloxacin N-oxide in haemodialysis patients with end-stage renal failure

Abstract: Six patients with end-stage chronic renal failure undergoing haemodialysis were given ofloxacin (600 mg) orally and blood samples were taken at intervals up to 32 h. In four patients samples were also taken before and after haemodialysis. Serum concentrations of ofloxacin, desmethyl ofloxacin and ofloxacin N-oxide were measured by HPLC. The drug was well tolerated. Mean pharmacokinetic parameters for ofloxacin were Cmax 5.5 h (S.D. 1.97 h), Tmax 3.9 h (S.D. 3.25 h), T1/2 28 h (S.D. 17.37 h), AUC0-24 83.1 mg/1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Many pharmacokinetic parameters of OFLX have been established in healthy (11) and renal failure (25) subjects. The present data show that concentration profiles of S-(-)-OFLX and R-(+)-OFLX in serum after oral (±)-OFLX administration in humans were almost equal to those of the racemic drug reported in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many pharmacokinetic parameters of OFLX have been established in healthy (11) and renal failure (25) subjects. The present data show that concentration profiles of S-(-)-OFLX and R-(+)-OFLX in serum after oral (±)-OFLX administration in humans were almost equal to those of the racemic drug reported in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, there exist species differences in OFLX glucuronidation, as the small amount of glucuronide excreted in urine by dogs and monkeys indicates (19). In humans, (±)-OFLX has been shown to undergo only limited metabolism with urinary excretion of small amounts of metabolites (desmethyl OFLX and OFLX N-oxide) and most of the administered drug is excreted unchanged in the urine (11,24,25).…”
mentioning
confidence: 99%
“…Demethyl-ofloxacin has moderate antibacterial activity and can represent 39 2 to 20% of ofloxacin concentrations. Such low metabolite concentrations are present even in renal failure that it is of negligible clinical importance (White et al 1987(White et al , 1988.…”
Section: Metabolismmentioning
confidence: 99%
“…The apparent t 1/2 values (approximately 8 h) for LVFX were also nearly equal to the values for healthy volunteers (1,13) and those for patients with human immunodeficiency virus infections (4). It has been reported that a small amount of ofloxacin is metabolized (10,17,18). In this study, for all treatment groups the percentages of LVFX recovered from urine within 24 h ranged from 80 to 90%, results identical to data in the review by Davis and Bryson (1) and indicating that the total systemic availabilities of LVFX for the four doses are nearly equal.…”
mentioning
confidence: 52%